The Influence of Leadership, Communication, and Staff Attitude on Hospital Operational Efficiency in East Jakarta - Briesha Aurevella Putri Satria; Innocentius Bernarto (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Hospital competition in Indonesia is increasing, requiring every institution to maintain sustainability through increased operational efficiency. Operational efficiency plays a crucial role in service quality, resource utilization, and hospital financial stability. This study aims to analyze the influence of leadership and communication on operational efficiency with staff attitudes as a mediating variable at ABC Hospital, East Jakarta. This study used a causal quantitative approach with Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis. The sample consisted of 204 healthcare workers at ABC Hospital. Data was collected using a 7-point Likert-scale questionnaire that had been tested for validity and reliability. The analysis included evaluation of the outer model, inner model, hypothesis testing, and Importance-Performance Map Analysis (IPMA). Leadership and communication significantly influenced staff attitudes. Staff attitudes significantly influenced operational efficiency and partially mediated the influence of leadership on operational efficiency. In addition, leadership also had a direct and significant influence on hospital operational efficiency. Therefore, improving leadership quality and strengthening staff professional attitudes are key strategies in sustainably improving the operational efficiency of ABC Hospital.